Simultaneously Toughening and Stiffening Elastomers with Octuple Hydrogen Bonding - Zhuo, Yizhi (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.